Engineering a functionality-integrated artificial cornea stromal Substitute: Janus bio-adhesive implant with a collagen-based multi-scale biomimetic skeleton - Miao Lei; Yue Ji; Shaohua Zhang; Bing Hou; Yi Lu; Jianguo Sun; Changsheng Liu; Xue Qu (Bioactive Materials, 2025)
Corneal transplantation presents an urgent demand for artificial cornea stromal substitutes (ACSs) with comprehensive functional design, spanning from material biology to clinical application. Here, we report the use of an engineering integration strategy to develop Janus ACSs with collagen-based multiscale biomimetic skeletons and tissue-adhesion. Specifically, the electro-assembly of collagen is employed to construct the skeleton of Janus ACS that mimics the microstructure and macroscopic morphology of native corneal stroma, ensuring the desired transparency, refractive power and adaptable shape. The bi-component ''bio-cement'' coating on the surface of skeleton, composed of 4-arm polyethylene glycol succinyl succinate and ε-polylysine, undergoes fast and mild amidation reactions driven by interfacial moisture, curing into a transparent hydrogel coating. The coating establishes a stable covalent connection between the corneal stroma and the skeleton, achieving immediate (<10 s) and stable tissue adhesion to adapt to the wet, dynamic mechanical environment of the eye. In vitro and in vivo studies further confirmed that the customized bio-adhesive Janus ACSs allow sutureless implantation and facilitate corneal epithelialization, stroma integration and reconstruction. A foraging behavior test highlighted the significant advantages of Janus ACSs in rapid vision recovery. The engineered integrated manufacturing of Janus ACSs potentially maximizes practicality while minimizing costs in applications.